Why Teachers Are Leaving Their Jobs: An Analysis of Attrition of Teachers in Malawi - Nyirenda, Penjani; Beri, Nimisha (International Journal of Psychosocial Rehabilitation, 2020)
In Malawi, on average, there is 1 teacher for every 70 learners. On top of this, teachers are leaving their jobs at their schools in search of better opportunities. This constant attrition is therefore a major challenge of the education sector, which is struggling as it is to provide quality education. This paper analyses the reasons why teachers are leaving their jobs in an attempt to understand the core problems at the heart of this phenomena. It consolidates key findings of several studies to identify six major reasons for teacher attrition. These are the “placeholder” status of teaching; teachers following their spouses; low salaries and incentives; poor living and working conditions; lack of promotions and; the HIV and AIDS pandemic. A major gap is the lack of a detailed retention strategy to keep teachers from leaving schools. It recommends greater stakeholder collaboration to support teachers by improving working conditions, improving the public perception of the teaching profession and providing more opportunities for career advancement.